Literature Review - Lemma, T.A. (Springer Verlag, 2018)
This chapter is intended to discuss the FDD methods in the area of power plants. However, apart from covering the methods applied to CCPs, it zooms into thermal systems in a wider perspective. The main benefits from this chapter is that it reveales possible research directions that reaffirm our choice of a specific method in Chap. 1. Further more, candidate areas for possible further research are also enumerated. Â© 2018, Springer International Publishing AG.